A wide angle chemical survey of the Sagittarius dwarf Spheroidal galaxy. Issue Volume 14:Issue S344(2019) (August 2018) - Sbordone, L.; Monaco, L.; Duffau, S.; Bonifacio, P.; Caffau, E.
Abstract: We present the status of an ongoing project to map the detailed chemical abundances of stars across the main body of the Sagittarius dwarf Spheroidal galaxy (Sgr dSph). The Sgr dSph is the closest known dwarf galaxy, and is being tidally destroyed by its interaction with the Milky Way (MW), leaving behind a massive stellar stream. Sgr dSph is a chemically outstanding object, with peculiar abundance ratios, clear center-outskirts abundance gradients, and spanning more than 3 orders of magnitude in metallicity. We present here detailed abundances from UVES@VLT spectra for more than 50 giants across 8 fields along the major and minor axes of Sgr dSph, and 5 more outside the galaxy main body, but possibly associated to its stellar stream.